PCR - RFLP patterns for the differentiation of the Fusarium species in virtue of ITS rDNA - Reza Kachuei; Mohammad Hossein Yadegari; N Safaie; SA Ghiasian; F Noorbakhsh; V Piranfar; sasan rezaie (Current Medical Mycology, 2015)
Background and Purpose: The Fusarium species are among the most important fungi in the medical, veterinary and agricultural fields. Materials and Methods: In the present study, 172 strains of these fungi have been analyzed. The high molecular weight DNAs were extracted from 23 reference strains as well as from 149 isolated Fusarium species. Using the designed nucleotide primers from rDNA of Fusarium species, PCR analysis was performed for the amplification of ITS regions. Afterwards, the location of the effective endonuclease enzymes has been evaluated within approximately 930 bp of rDNA sequence. Results: Through the selected enzymes including; HhaI, MspI, TaqI and FaqI, the mentioned Fusarium species have been divided into 33 groups. The first three enzymes were able to classify Fusarium species into 23 groups of which 19 groups included one member, one group included two members and three groups included three members of the Fusarium species. This study also revealed the possibility in the identification of F. semitectum, F. solani complex, F. pseudograminearum, F. nisikadoi, F. coeruleum and F. acuminatum species by one unique enzyme. In addition, our study indicated the ability of the differentiation of F. Compactum from F. equiseti. Conclusion: As Compared to previous studies with more endonuclease enzymes and with limited in identifications, the ITS-RFLP patterns reported here an attempted to evaluate most of the Fusarium species successfully.